1990
DOI: 10.1080/0742-969x.1990.11882684
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Survival Time in Terminal Cancer Patients: An Impedance to Hospice Admissions?

Abstract: Accurate estimation of survival time in terminal cancer patients is difficult yet may provide useful information. A historical prospective study on 172 patients admitted to a home based hospice service was performed to determine which variables were best correlated with survival time. Mean and median survival were 48 and 22 days, respectively, representing a highly skewed distribution of life span in this sample. As age increased, survival time decreased. All Activities of Daily Living (ADLs) recorded (Bathing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
2
27
1
Order By: Relevance
“…Previous studies of single hospices, both in the United States and abroad, have found median survival times of 11 to 30 days, [26][27][28][29][30][31][32][33] and those based on data from multiple hospices have found survival times of 25 to 35 days. 3,10,34 These studies have been limited, however, by their focus on inpatients, by their exclusion of patients with diagnoses other than cancer, or by their incomplete or short follow-up or small or nonrepresentative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of single hospices, both in the United States and abroad, have found median survival times of 11 to 30 days, [26][27][28][29][30][31][32][33] and those based on data from multiple hospices have found survival times of 25 to 35 days. 3,10,34 These studies have been limited, however, by their focus on inpatients, by their exclusion of patients with diagnoses other than cancer, or by their incomplete or short follow-up or small or nonrepresentative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen articles were identified which examined the prognostic indicators of survival. They are listed in table 3 ( 7, 1 0, 1 1 , 16,[18][19][20][25][26][27][28][29][30][31][32][33][34][35].…”
Section: 16-24)mentioning
confidence: 99%
“…Studies have shown that physicians usually overestimate survival time [13,22,27,28]. In 1982, the Louis Harris polling group conducted a national survey for a presidential commission on bioethics.…”
Section: Medical Futility and Appropriate Carementioning
confidence: 99%